La Cantalera: an exceptional window onto the vertebrate biodiversity of the Hauterivian-Barremian transition in the Iberian Peninsula - Canudo, J.I.; Aurell, M.; Gasca, J.M.; Badiola, A.; Blain, H.-a.; Cruzado-Caballero, P.; Gomez-Fernández, D.; Moreno-Azanza, M.; Parrilla, J.; Rabal-Garces, R.; Ruiz-Omenaca, J. I. (Journal of Iberian Geology, 2010)
La Cantalera is an accumulation site for fossil vertebrates consisting mainly of teeth and isolated postcranial remains. It has the greatest vertebrate biodiversity of any site from the Hauterivian-Barremian transition in the Iberian Peninsula. Up to now, 31 vertebrate taxa have been recognized: an osteichthyan (Teleostei indet.), two amphibians (Albanerpetonidae indet. and Discoglossidae indet.), a chelonian (Pleurosternidae? indet.), a lizard (Paramacellodidae? indet.), four crocodylomorphs (cf. Theriosuchus sp., Bernissartiidae indet., Goniopholididae indet., cf. Lisboasaurus sp.), two pterosaurs (Istiodactylidae? indet., Ornithocheiridae? indet.), four ornithopod dinosaurs (Iguanodontoidea indet., Hadrosauroidea? indet., “Hypsilophodontidae” indet., Rhabdodontidae? indet.), a thyreophoran (Polacanthidae indet.), a sauropod (Euhelopodidae indet.), eleven theropods (Carcharodontosauridae? indet., Baryonychinae indet., aff. Paronychodon sp., Maniraptora indet. 1-3, Dromaeosaurinae indet. 1-3, Velociraptorinae indet., Avialae? indet.) and three or four multituberculate mammals (Cantalera abadi, Eobaatar sp., Plagiaulacidae or Eobaataridae gen. et sp. indet., “Plagiaulacida” indet.). Nine ootaxa have also been distinguished at the site of La Cantalera. Oofamilies assigned to dinosaurs (Elongaloolithidae, Prismatoolithidae, cf. Spheroolithidae), to crocodiles (Krokolithidae) and eggshells of two oofamilies incertidae sedis are represented. This association is consistent with the record of bone and tooth remains from the site. La Cantalera was formed in a marshy environment where there was an intermittent body of water. The great majority of the vertebrate fossil remains lack evidence of transport, so the preserved association is a good representation of the vertebrate ecosystem in or around the marshy area of La Cantalera. The vertebrate association of La Cantalera displays certain differences with respect to those from lacustrine environments of the Hauterivian-Barremian transition of the Iberian Range. These differences include, for example, the absence of Chondrichthyes, the merely token presence of the osteichthyans, the scarcity of chelonians, the presence of exclusively multituberculate mammals, the lower diversity of sauropods and the greater diversity of theropods.